2016
DOI: 10.1104/pp.15.01911
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the rice ADPglucose transporter (OsBT1) indicates the presence of regulatory processes in the amyloplast stroma that control ADPglucose flux into starch

Abstract: Previous studies showed that efforts to further elevate starch synthesis in rice (Oryza sativa) seeds overproducing ADP-glucose (ADPglc) were prevented by processes downstream of ADPglc synthesis. Here, we identified the major ADPglc transporter by studying the shrunken3 locus of the EM1093 rice line, which harbors a mutation in the BRITTLE1 (BT1) adenylate transporter (OsBt1) gene. Despite containing elevated ADPglc levels (approximately 10-fold) compared with the wild-type, EM1093 grains are small and shrive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 48 publications
2
47
0
Order By: Relevance
“…4 G and E). Furthermore, the chain-length distributions in amylopectin exhibited a small increase in the abundance of branches with degrees of polymerization (DP) in the range 10-20 and a small decrease in chains with DP in the range [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] (Fig. S5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 G and E). Furthermore, the chain-length distributions in amylopectin exhibited a small increase in the abundance of branches with degrees of polymerization (DP) in the range 10-20 and a small decrease in chains with DP in the range [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] (Fig. S5).…”
Section: Discussionmentioning
confidence: 99%
“…It is further proposed that the starch biosynthetic enzymes in the protein complex can exert a constraining effect on PPDK and AGPase to control the partitioning of ADPGlc into lipid or starch. It is known that uptake of ADPGlc by the plastid and the activity of the major SS enzymes do not limit carbon flux into starch, but that other constraints within the stroma control the flux into starch (36).…”
Section: Discussionmentioning
confidence: 99%
“…Flipse et al (1996) suggested that, except for GBSSI, the amylose content of starch potentially correlates with the availability of ADP-Glc and the limited physical space available within the matrix of amylopectin. However, even though the BRITTLE1 (Bt1) gene was overexpressed in an up-regulated AGPase background, generating a rice line with enhanced ADP-Glc synthesis and import into amyloplasts, only a limited carbon flow into starch was observed (Cakir et al, 2016). Therefore, substrate amount is not the rate-limiting step for increasing amylose.…”
Section: Regional Distribution Of Three Sbe Isoforms In Developing Enmentioning
confidence: 99%
“…S2, A and C). Cakir et al (2016) reported that, when enriched ADP-Glc supply was provided, starch content could be elevated somewhat (about 10%) in the condition that the activity of starch synthase was kept unchanged. This indicated that starch content could be elevated even though the amounts and activity of starch synthase including GBSSI were not increased and only a limited amount of starch increase was detected.…”
Section: Regional Distribution Of Three Sbe Isoforms In Developing Enmentioning
confidence: 99%
“…Genetic studies in maize, rice, and barley have shown that the predominant cytosolic isoform of AGPase is responsible for controlling the flow of carbon into storage starch in the endosperm [150][151][152][153]. ADP-Glc that is produced in the cytosol is transported into the amyloplast for starch synthesis via an ADP-Glc/ADP antiporter (termed BT1) located in the plastid inner envelope membrane [154][155][156]. The presence of extra-plastidial AGPase is not confined to domesticated cereals, but seems to be a unique feature of the endosperms of the Poaceae.…”
Section: Agpase: the First Committed Step In Starch Biosynthesismentioning
confidence: 99%